Public-Private Partnerships for Health in Vietnam : Issues and Options - Le, Sang Minh; Govindaraj, Ramesh; Bredenkamp, Caryn (Washington, DC: World Bank, 2020)
This book describes the nature of public-private partnerships (PPPs) in the health sector in Vietnam. It defines health-related PPPs, describes their key characteristics, and develops a taxonomy of the different types of PPPs that exist in practice, illustrated by international examples. It also assesses the regulatory and institutional framework for the health PPP program in Vietnam, as well as financing and accountability mechanisms for PPPs at its national and subnational levels. It provides an overview of the PPP project pipeline in Vietnam and analyzes important issues in the health PPPs’ design, preparation, and implementation, using eight case studies involving projects in different phases of the project cycle. This book also examines barriers that have hampered the successful design and implementation of health care PPPs in Vietnam. These barriers may be broadly categorized as barriers in the PPP policy and regulatory framework, in the public sector, in the private sector, and in the financial sector. It proposes feasible and actionable recommendations so that the government can consider tackling the identified barriers and advance the successful design and implementation of health PPPs.